Adjunctive sertraline for asymptomatic cryptococcal antigenemia: A randomized clinical trial. (16th May 2020) - Boulware, David R; Nalintya, Elizabeth; Rajasingham, Radha; Kirumira, Paul; Naluyima, Rose; Turya, Fred; Namanda, Sylvia; Rutakingirwa, Morris K; Skipper, Caleb P; Nikweri, Yofesi; Hullsiek, Kathy Huppler; Bangdiwala, Ananta S; et al.
Abstract: Cryptococcal antigen (CrAg) screening in HIV-infected persons with CD4 < 100 cells/µl can reduce meningitis and death, yet preemptive fluconazole therapy fails in ∼25%. Sertraline has in vitro and in vivo activity against Cryptococcus and is synergistic with fluconazole in mice. We evaluated the efficacy and safety of sertraline in asymptomatic cryptococcal antigenemia. We conducted a randomized trial of asymptomatic CrAg-positive Ugandans from November 2017 to February 2018. All subjects received WHO standard therapy of fluconazole 800 mg for 2 weeks, then 400 mg for 10 weeks, then 200 mg through 24 weeks. Participants were randomized to receive adjunctive sertraline or placebo, given in once-weekly escalating 100 mg/day doses up to 400 mg/day, which was then given for 8 weeks, then tapered. The primary endpoint was meningitis-free 6-month survival. The data and safety monitoring board halted the trial after 21 subjects were enrolled due to safety concerns. Meningitis-free 6-month survival occurred in 9 of 11 of placebo participants and 10 of 10 of sertraline participants. However, seven serious adverse events (SAEs) occurred ( n = 4 sertraline group; n = 3 placebo group). Three SAEs in the sertraline group presented with psychosis and aggressive behavioral changes with one meeting Hunter's criteria for serotonin syndrome while receiving 200 mg/day sertraline. Two transient psychoses were associated with antecedent fluconazole and sertraline interruption. The serotonin syndrome resolved within 1 day, but psychosis persisted for 4 months after sertraline discontinuation. Sertraline was associated with excess SAEs of psychosis. Due to early stopping, we were unable to determine any efficacy for cryptococcal antigenemia.